Cryo-EM structure of the Mycobacterium abscessus F1-ATPase - Wong, Chui Fann (2023)
The cases of lung disease caused by non-tuberculous mycobacterium Mycobacterium abscessus (Mab) are increasing and not reliably curable. Repurposing of anti-tuberculosis inhibitors brought the oxidative phosphorylation pathway with its final product ATP, formed by the essential F1FO-ATP synthase (subunits α3:β3:γ:δ:ε:a:b:b':c9), into focus as an attractive inhibitor target against Mab. Because of the pharmacological attractiveness of this enzyme, we generated and purified a recombinant and enzymatically active Mab F1-ATPase complex, including subunits α3:β3:γ:δ:ε (MabF1-αβγδε) to achieve mechanistic, regulatory, and structural insights. The high purity of the complex enabled the first cryo-electron microscopy structure determination of the Mab F1-ATPase complex to 7.3 Å resolution. The enzyme showed low ATP hydrolysis activity, which was stimulated by trypsin treatment. No effect was observed in the presence of the detergent lauryldimethylamine oxide.